2012
DOI: 10.1002/app.38023
|View full text |Cite
|
Sign up to set email alerts
|

Immobilization of Candida lipolytica lipase on macroporous beaded terpolymers with epoxy groups

Abstract: A series of macroporous beaded terpolymers with epoxy groups were synthesized by suspension polymerization with glycidyl methacrylate (GMA), ethylene glycol dimethacrylate (EGDMA), and the third monomers including styrene, methyl methacrylate, n-butyl acrylate (BA), butyl methacrylate (BMA), and 2-hydroxyethyl methacrylate for immobilization of Candida lipolytica lipase. The effect of various third monomers on loading and activity recovery of immobilized lipase were studied. Terpolymers with BA as the third mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…[5,8,9] Fluorine-based monomers, such as pentafluorostyrene (PFS), have also been used on the manufacture of functionalized polymer materials. [20][21][22][23][24] However, most studies perform the polymer synthesis and functionalization in solution, which is not ideal regarding the production of nanoparticles and enzyme supports.…”
Section: Introductionmentioning
confidence: 99%
“…[5,8,9] Fluorine-based monomers, such as pentafluorostyrene (PFS), have also been used on the manufacture of functionalized polymer materials. [20][21][22][23][24] However, most studies perform the polymer synthesis and functionalization in solution, which is not ideal regarding the production of nanoparticles and enzyme supports.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, their high cost and difficulty of recycle are also concerned for their industrial applications. An effective method to solve the above problems was the immobilization of cellulases , including adsorption, crosslinked enzyme aggregates, embedding, and covalent binding . Some researchers immobilized cellulase on different carriers, and the obtained immobilized cellulase exhibited excellent residual activities .…”
Section: Introductionmentioning
confidence: 99%
“…A good choice to overcome these questions is using porous terpolymers as the supports instead of inorganic and organic materials. Duan and coworkers chose glycidyl methacrylate (GMA) as the functional monomer of porous terpolymer to immobilize Candida lipolytica lipase, and the results showed that the pore structure of terpolymers was beneficial for immobilization of enzyme. Cao et al immobilized cellulase on a pH‐sensitive polyacrylate terpolymer (P MDB ) and they found that the terpolymer had better immobilization efficiency.…”
Section: Introductionmentioning
confidence: 99%